Case Report : Low Level ImmunoglobulinG (IgG) in reinfection COVID-19 case - Enny Nugraheni; Debbie Rizqoh; Annelin Kurniati; Lusiana Astuti; Mulya Sundari; Etty Febrianti (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Million people have infected the SARS-CoV-2 epidemic, which is currently spreading. We describe a confirmed COVID- 19 patient whose oropharyngeal swab test for SARS-CoV-2 RNA and have positive PCR test results after 8 weeks proclaim negative result of PCR test for SARS-COV-2. ImmunoglobulinG was not detected during the initial illness. In this study, we discuss the potential role of low IgG in cases of reinfection.